What Makes the Genre of Lyric Compelling? - Pálinkás, Katalin (Hungarian Journal of English and American Studies, 2021)
Book review: Culler, Jonathan. Theory of the Lyric. Cambridge, MA: Harvard UP, 2015. x + 391 pages. ISBN 978-0-674-74426-4. Hb. 41.